A primate-specific short GluN2A-NMDA receptor isoform is expressed in the human brain - Hannah Warming; Chrysia-Maria Pegasiou; Aleksandra P. Pitera; Hanna Kariis; Steven D. Houghton; Ksenia Kurbatskaya; Aminul Ahmed; Paul Grundy; Girish Vajramani; Diederik Bulters; Xavier Altafaj; Katrin Deinhardt; et al. (Molecular Brain, 2019)
Abstract Glutamate receptors of the N-methyl-D-aspartate (NMDA) family are coincident detectors of pre- and postsynaptic activity, allowing Ca2+ influx into neurons. These properties are central to neurological disease mechanisms and are proposed to be the basis of associative learning and memory. In addition to the well-characterised canonical GluN2A NMDAR isoform, large-scale open reading frames in human tissues had suggested the expression of a primate-specific short GluN2A isoform referred to as GluN2A-S. Here, we confirm the expression of both GluN2A transcripts in human and primate but not rodent brain tissue, and show that they are translated to two corresponding GluN2A proteins present in human brain. Furthermore, we demonstrate that recombinant GluN2A-S co-assembles with the obligatory NMDAR subunit GluN1 to form functional NMDA receptors. These findings suggest a more complex NMDAR repertoire in human brain than previously thought.